Inspecting Coding Dependency in Layered Video Coding for Efficient Unequal Error Protection - Zakerinasab, Mohammad Reza; Mea Wang (Proceedings of the International Conference on Distributed Computing Systems, 2015)
To improve the quality of video streaming subject to video bitrate or communication channel capacity, a high-quality video is encoded into multiple layers of unequal importance. Layers that provide higher quality rely on the previous layers for successful reconstruction of transmitted video packets. Hence, if a video packet in a reference layer is corrupted or lost during transmission, the dependent layers cannot be reconstructed successfully, and the resources consumed to transmit them are wasted. To address this problem, unequal error protection (UEP) techniques have been proposed to provide appropriate level of protection to each layer according to their importance. Nonetheless, the importance of a piece of video content is determined by not only the layering structure, but also coding dependency imposed by encoding decisions. In this paper, based on a deep inspection of coding and prediction in SVC (a layered video coding standard) and an analysis of seven real SVC videos, we conclude that macro block-level coding dependency will provide a more accurate importance measure when applying UEP to protection video packets in noisy channels.